Hypertension and Diabetes Mellitus: Coprediction and Time Trajectories. Issue 3 (March 2018) - Tsimihodimos, Vasilis; Gonzalez-Villalpando, Clicerio; Meigs, James B.; Ferrannini, Ele
Abstract : Type 2 diabetes mellitus and hypertension overlap in the population. In many subjects, development of diabetes mellitus is characterized by a relatively rapid increase in plasma glucose values. Whether a similar phenomenon occurs during the development of hypertension is not known. We analyzed the pattern of blood pressure (BP) changes during the development of hypertension in patients with or without diabetes mellitus using data from the MCDS (Mexico City Diabetes Study; a population-based study of diabetes mellitus in Hispanic whites) and in the FOS (Framingham Offspring Study, a community-based study in non-Hispanic whites) during a 7-year follow-up. Diabetes mellitus at baseline was a significant predictor of incident hypertension (in FOS, odds ratio, 3.14; 95% confidence interval, 2.17–4.54) independently of sex, age, body mass index, and familial diabetes mellitus. Conversely, hypertension at baseline was an independent predictor of incident diabetes mellitus (in FOS, odds ratio, 3.33; 95% CI, 2.50–4.44). In >60% of the converters, progression from normotension to hypertension was characterized by a steep increase in BP values, averaging 20 mm Hg for systolic BP within 3.5 years (in MCDS). In comparison with the nonconverters group, hypertension and diabetes mellitus converters shared a metabolic syndrome phenotype (hyperinsulinemia, higher body mass index, waist girth, BP, heart rate and pulse pressure, and dyslipidemia). Overall, results were similar in the 2 ethnic groups. We conclude that (1) development of hypertension and diabetes mellitus track each other over time, (2) transition from normotension to hypertension is characterized by a sharp increase in BP values, and (3) insulin resistance is one common feature of both prediabetes and prehypertension and an antecedent of progression to 2 respective disease states. Abstract : Supplemental Digital Content is available in the text.